The reliability of a composite biodiversity indicator in predicting bird species richness at different spatial scales. (December 2016) - Valerio, Francesco; Basile, Marco; Balestrieri, Rosario; Posillico, Mario; Di Donato, Sergio; Altea, Tiziana; Matteucci, Giorgio
Highlights: We used species distribution modelling to implement a bird biodiversity indicator that we found highly predictive of bird species richness. The biodiversity indicator was tested at three spatial scales: small, medium and large. Testing results were used to infer about the reliability and usefulness of such an indicator in the broad context of biological monitoring and conservation planning. We believe that the potential of our indicator is provided by the consolidated statistical and modelling techniques implemented and by its adaptability to different taxa and regions. Abstract: Several biodiversity features can be linked to landscape heterogeneity, that, in turn, can be informative for management and conservation purposes. Usually, the more the landscape is complex the more the biodiversity increases. Biodiversity indicators can be a useful tool to assess biodiversity status, in function of landscape heterogeneity. In this study, we developed a biodiversity indicator, based on Shannon diversity index and built from distribution maps of protected species. With such an approach, we seek to evaluate the feasibility of using a combination of target species as a surrogate for assessing the status of the whole bird community. Our approach was spread over multiple spatial scales, to determine which was the most informative. We selected four species protected by European regulation and generated a presence-absence map from species distribution modelling. We, therefore, used the FRAGSTATS biodiversity metric to calculate Shannon index for the overlapped presence-absence maps, at two spatial scales (500 m and 1000 m). Then, the relationships with the whole community was assessed through generalised least square models, at the spatial scale of 4 ha, 9 ha and 25 ha. Results showed that the higher rate of variability of community was explained by the biodiversity indicator at 1000 m scale. Indeed, the more informative spatial scale for the whole bird community was 9 ha. In addition, a pattern emerged about the relationships between biodiversity indicator and community richness, that is worth of further research. Our study demonstrates that the usefulness of surrogate species for biodiversity and community assessment can become clear only at a certain spatial scales. Indeed, they can be highly predictive of the whole community, and highly informative for conservation planning. Moreover, their use can optimize biodiversity monitoring and conservation, focusing on a small number of noteworthy species.